Komunikasi Seni Hadrah Majelis Ahbaabul Musthofa Yogyakarta - Nida Marufah (UIN Antasari Banjarmasin, 2021)
Ahbaabul Musthofa has big role in the development of da'wah in Special Region of Yogyakarta. Beside having a very broad of worshipers covering all districts in Yogyakarta, this hadrah group as a performer of Ahbaabul Musthafa assembly also has a good track record with Habib Shaykhs throughout Indonesia. This makes the group reference for most hadrah groups in Yogyakarta. As a media of da'wah, there are messages to be conveyed through the hadrah. Not only in the performance of the hadrah, it also represented in symbols through the entire of this assembly. By ethnographic analysis, we try to explore the problems in terms of culture and communication. Based on research, being a dominant worshipers in these assembly was apparently unable to guarantee the Syekher Mania Community understood the symbols and their meanings. The results showed that besides being a place for friendship and media to increase love for the Prophet Muhammad, hadrah also being a form of self-servitude to Allah through fun worship, respect for the presence of the Prophet Muhammad, symbolizing the atmosphere of joy, peace of mind, faith, simplicity, sincerity, and determination in devotion to Allah.KEYWORDS: Hadrah, symbols, meanings of hadrah symbols, Ahbaabul Musthofa Yogyakarta.